The Word of the Sacrament. Supreme Realization of Faith - Daelemans, SJ, Bert (Estudios Eclesiásticos. Revista de investigación e información teológica y canónica, 2016)
In intimate connection to Marta García Fernández’s article on «the sacramentality of the Word», also in this volume, the present article proposes to deepen this fructiferous relationship between Word and sacrament, but now from the perspective of the sacrament. First, commenting on basic texts by St Augustine and Karl Rahner, we present the rich intuition of the sacrament as word, as the word par excellence. Second, we examine the function of the word within the sacrament as forma sacramenti and condensed faith. Finally, we propose the sacramentality of liturgical silence as «sound box» for the Word.